2023
DOI: 10.1590/1519-6984.248708
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of curcuminoids against head and neck cancer HNO97 cell line

Abstract: Oral squamous cell carcinoma (OSCC) is a malignant tumour of Head and Neck Cancer (HNC). The recent therapeutic approaches used to treat cancer have adverse side effects. The natural agents exhibiting anticancer activities are generally considered to have a robust therapeutic potential. Curcuminoids, one of the major active compounds of the turmeric herb, are used as a therapeutic agent for several diseases including cancer. In this study, the cytotoxicity of curcuminoids was investigated against OSCC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Curcuminoids consist of diferuloylmethane (curcumin), desmethoxycurcumin, and bisdemethoxycurcumin 15 . A study in human oral squamous cell carcinoma (HNO97 cell line) showed inhibition in proliferation, morphological changes (apoptosis‐like), alterations in cell cycle distribution, and DNA damage 15 . Also investigators found apoptosis induction and suppression of colony‐forming ability in a time‐dependent manner 15 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Curcuminoids consist of diferuloylmethane (curcumin), desmethoxycurcumin, and bisdemethoxycurcumin 15 . A study in human oral squamous cell carcinoma (HNO97 cell line) showed inhibition in proliferation, morphological changes (apoptosis‐like), alterations in cell cycle distribution, and DNA damage 15 . Also investigators found apoptosis induction and suppression of colony‐forming ability in a time‐dependent manner 15 …”
Section: Resultsmentioning
confidence: 99%
“…Those with activity in skin tumors and NMSC are resveratrol, 14 cryptolepine, apigenin, 13 and curcumin (Diferuloylmethane) 15 . Curcumin has been particularly evaluated on SCC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations